REVITALISASI TRADISI DAN POLITIK IDENTITAS: DIALEKTIKA KRISTIANITAS DI MALUKU - Steve Gerardo Christoffel Gaspersz; Nancy Novitra Souisa (IAIN Ambon, 2021)
One indicator in examining religious dynamics is the formation of a religious institution and its existence in its history. This article attempts to analyze the historical dynamics of the establishment of the religious institution, namely the Protestant Church of Maluku (GPM) in the Maluku (Ambon) socio-cultural context. The scrutiny for exploring documents and constructing some interpretations of them is carried out using the social hermeneutic method to understand (verstehen) the dialectic between ideal principles through the internalization of Christian religious teachings and responses to various socio-cultural-political changes in the context in which it lives. The hermeneutic analysis is carried out to obtain a comprehensive understanding about the existence and religious orientation of the GPM, which is also influenced by the dialectic of encounters with various other identities. Keywords: identity politics, Christianity, tradition, modernity